Lysosomal fusion and SNARE function are impaired by cholesterol accumulation in lysosomal storage disorders. (2nd November 2022) - Fraldi, Alessandro; Annunziata, Fabio; Lombardi, Alessia; Kaiser, Hermann‐Josef; Luis Medina, Diego; Spampanato, Carmine; Olind Fedele, Anthony; Polishchuk, Roman; Sorrentino, Nicolina Cristina; Simons, Kai; Ballabio, Andrea
Abstract : Partial Retraction of: The EMBO Journal (2010) 29: 3607–3620. DOI: 10.1038/emboj.2010.237 | Published online 24 September 2010 Journal statement The journal contacted the authors in February 2022 about potential image insertions and duplications in Fig 4A and 4E. In the absence of source data, the authors are retracting Fig 4A, the lower panel of Fig 4E (LAMP1 immunoblot), and the following statements in the text that rely on these data: "Quantitative analysis showed that the percentage of Flotillin‐1 associated with DRMs was increased in LSD endolysosomal membranes (Figure 4A), indicating an increased amount of cholesterol‐enriched regions in these membrane samples." "LAMP1 also displayed a similar distribution profile in WT and LSD cells (Figure 4E)". Author statement The authors could not verify the aberrations in panel A of Fig 4 and the lower immunoblot (LAMP1) of 4E because the original source data are no longer available (12 years after publication, which is beyond the institute's 10‐year data retention policy). The authors wish to clarify that the main conclusions of the paper are not affected by the retraction of Figure panels 4A and 4E for the following reasons: Figure panel 4A supports the observation that there are increased cholesterol‐enhanced regions in LSD samples. This finding is also supported by data provided in figs 4B, 4C and 4D. Figure panel 4E: The LAMP1 blot in Fig 4E shows that the distribution of protein normally excluded from DRMs is not altered between Wt and LSD samples. This result is also supported by the upper blot in this panel (Transferrin receptor). The authors apologize for these errors and agree with this corrigendum; no response could be obtained from AL.